Discovery and SAR study of 3-(tert-butyl)-4-hydroxyphenyl benzoate and benzamide derivatives as novel farnesoid X receptor (FXR) antagonists. Issue 19 (1st October 2015) - Song, Kebiao; Xu, Xing; Liu, Peng; Chen, Lili; Shen, Xu; Liu, Junhua; Hu, Lihong
Graphical abstract: Abstract: 3-( tert -Butyl)-4-hydroxyphenyl 2, 4-dichlorobenzoate (1 ) was discovered in our in-house high throughput screening as a moderate FXR antagonist. To improve the potency and the stability of the hit1, forty derivatives were synthesized and SAR was systematically explored. The results turn out that replacing the 2, 4-dichlorophenyl with 2, 6-dichloro-4-amidophenyl shows great improvement in potency, replacing the benzoate with benzamide shows improvement in stability and slight declining of potency and 3-( tert -butyl)-4-hydroxyphenyl unit is essential in obtaining the FXR antagonistic activity.